Efficacy and safety of medroxyprogesterone acetate on noninvasive ventilation -treated exacerbated COPD patients: a double-blind randomized clinical trial - Mohsen Gholinataj Jelodar; Mohammadreza Malek-Ahmadi; Adeleh Sahebnasagh; Farhad Mohammadi; Fatemeh Saghafi (BMC Pulmonary Medicine)
Abstract Background In acute exacerbation periods of chronic obstructive pulmonary disease (COPD), patients may experience hypoxemia or hypercapnia. Noninvasive ventilation (NIV) and respiratory stimulant drugs are used to treat this condition. Medroxyprogesterone acetate (MPA) can cross the blood-brain barrier and cause breathing stimulation and hyperventilation. This study was conducted to investigate the effectiveness of MPA in hypercapnic exacerbated COPD patients and the possibility of faster weaning of patients from NIV. Materials and methods This double-blind clinical trial was conducted on consecutive exacerbated COD patients referred to Shahid Rahnemoun Hospital, Yazd, Iran, from February 2022 to August 2022. Through a block randomized sampling method with a 1:1 allocation ratio, 58 eligible patients with hypercapnic exacerbated COPD on NIV were divided into two study groups: the intervention (treated with MPA 10 mg every 8 h) and the control (treated with placebo). The clinical and arterial blood gas (ABG) parameters were investigated in both groups. Results Out of 50 patients, 27 and 23 intervention and control arms cases were analyzed. Although there was a significant difference in the amount of ABG parameters during the study in each group, there was no statistically significant difference between the two groups. Also, There was no significant difference in the total weaning rate of the patients in the two groups. Despite the higher number of early weaning in the MPA group, no significant difference was reported between the two groups in this regard. In addition, there was no difference between the two groups in the rate of ICU hospitalization, the length of stay of hospitalization and ICU, and the mortality rate. Conclusion The administration of MPA has not improved clinical and laboratory results, and MPA is not superior to placebo in the weaning process of patients undergoing NIV. Trial registration IRCT20190810044500N21 (01/02/2022), (https//irct.behdasht.gov.ir/user/trial/59402/view)